Network analysis and design at Teruntum Complex - Afiq, Lamaznun (2012)
As a networking student,it is important and compulsory to have some basic knowledge of networking knowledge about the network design,know how to make an analysis of network design and know how to implement or apply the network. Network architecture is a design of a communications network;it is a framework for the specifications of a network’s physical components and their functional organization and configuration,its operational principles and procedures as well as data formats used in its operation.Meanwhile a computer network,often simply referred to as a network,is a collection of hardware components and computers interconnected by communications channels that allow sharing of resources and information.Networks may be classified according to a wide variety of characteristics such as the medium used to transport the data, communications protocol used,scale,topology,and organizational scope.The rules and data formats for exchanging information in a computer network are defined by communications protocols.For my project which is Network analysis and design at Teruntum complex.Overall of this project is based on analysis on network performance in increasing the network performance at the selected area itself by referring to graph and what we can interpret from the graph that being produced.This analysis using Opnet IT Guru simulation tools that will be explained more throughout this report.